Between Styria and Bohemia. On the Sphere of Influence of the Kapfenberg Line of the House of Stubenberg in the Early Modern Age (Theatrum historiae, 2023)
The eminent Styrian aristocratic House of Stubenberg appears only marginally in the interpretation of the history of the Czech Lands. This article follows up on the author’s previous research into the work of the members of this house in Bohemia in the early modern age and links it with the facts known to Austrian historiography. Wolfgang von Stubenberg (d. 1556), the lord of Kapfenberg, who became a member of the Bohemian estates and the owner of the Nové Město nad Metují manor, was a remarkable type of a landlord who not only excelled in enhancing his landholdings and making them more profitable, but was also a skilled organiser in the wider context. This aspect of his personality was apparent not only in his economic skills but also in his family’s lifestyle. Over time, the Stubenberg clan thus introduced to Bohemian society three generations of leading Styrian aristocrats with experience of the broader environment of Central Europe and humanist Italy. Their economic background, spanning different regions and also comprising the key topic for interpretation, was therefore not used solely as a means of generating income and strengthening the position of the clan. It also facilitated mutual contacts and exchanges of an intellectual, cultural, and spiritual nature. The estates of the House of Stubenberg in Bohemia, the gradual extension of which went hand in hand with the increasing importance of these holdings and with the family’s integration into Bohemian society, were only dissolved as a result of confiscation and re-Catholicisation in the 1620s. The Stubenberg era faded during the Thirty Years’ War, with the former officials and servants remaining in contact with the family members in exile.
Keywords: Bohemia; Styria; early modern era; House of Stubenberg; economic history